STRATEGI DINAS PARIWISATA DALAM MENGEMBANGKAN OBJEK WISATA PANTAI PESONA KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS - Sri Mutiara Rizki; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Bengkalis regency has many potentials with various tourism objects such as natural and cultural tourist attractions are quite interesting that can be developed further as national tourism objects, one of them is Pantai Pesona North Rupat sub-district of Bengkalis regency. The government has conducted promotional activities and provided infrastructure facilities but there still very limited so it needs more development strategies in order to increase the interest of tourists.The theory concept used in this research is Theory of Sondang P Siagian (2012), SWOT analysis. The method used in this research is qualitative method by using descriptive approach. Data will be collected by using interview and documentation techniques.The results of this study indicate that the development strategy which carried out by the government of Bengkalis regency has not been maximized. This is can be seen from the unavailability of adequate facilities and infrastructures. The factor are human resources and financial resources. In developing this tourism object, cooperation with related parties is needed, furthermore the government should improve the quality of work, especially in utilizing the time.Keywords: Strategy, Development, Tourism Object